Analysis of Factors Affecting The Value of Indonesian Cocoa Exports 2003-2017 - Irawan, Wahyu Budhi (Jurnal Ilmu Ekonomi Terapan, 2019)
This study aims to analyze the effect of the Indonesian Kakao Export (NE), International price (HI), Domestic price (HD), Land (LL) on the Indonesia in 2003 - 2017. The data used in this study are secondary data. To analyze the influence of NE on the inequality of income On Indonesia in 2003 - 2017, the method of calculating the Gini Ratio and panel data regression analysis method are combined, which is a cross section of data with 10 provinces in Sumatra Island and time series data with annual data, 2007 - 2017. The results of the study show that the right regression model used is the fixed effect model. With the results of the Human Development Index (HDI) negatively affecting the inequality of provincial income distribution on the island of Sumatra in 2007 - 2017, Population (JP) has a positive effect on the inequality of provincial income distribution on Sumatra Island in 2007-2017 and the Provincial Minimum Wage negatively affected the imbalance of provincial income distribution on Sumatra Island in 2007 - 2017. Keywords: : Inequality of Income Distribution (Gini Ratio), Human Development Index (HDI), Population (JP), Provincial Minimum Wage (UMP). JEL: C00; F14